Dark Web and Cyber Scams: A Growing Threat to Online Safety - Arthan, Nagaraju; Kacheru, Goutham; Bajjuru, Rohit (International Journal of Multidisciplinary Sciences and Arts, 2023)
Internet as of now can be considered, and often is, a part of people’s lives, a continuation of its existence; the same can be said about Dark Web: Indeed, when I first applied the analysis to the opportunity sample, with the blink of an eye, it can be readily deduced that this type belongs to the high opportunity type as well as the high threat type. Where in its so-called objectives of private investigations it has assigned the alibi for the mask of its authorizing it now becomes an opened invitation for unlawful activities. This papers therefore seeks to identify the dark Web and some of the positive attributes and some of the negative externalities that are inevitably associated with any attempted formal classification of access to and control over browsers. The following are threats that exist within the platform in the above said area described as attacks, exploits and malwares. They also categories type of kind’s offence in the Dark Web in other to let more people know about existence of the areas and how to protect yourself.